Hybrid NN /FEM analysis of the elastoplastic plane stress problem - Waszczyszyn, Zenon; Pabisek, Ewa (Computer Assisted Methods in Engineering and Science, 1999)
The back-propagation neural network was trained off line in order to simulate operation of the return mapping algorithm. Selection of patterns and the neural network training as well as testing processes are discussed in detail. The network was incorporated into the FE computer code ANKA as a neural procedure. The hybrid neural-network/finite-element-method program ANKA-H was used for the analysis of two elastoplastic plane stress examples: i) perforated tension strip, ii) notched beam. The results of computations point out quite good accuracy of the hybrid analysis. Some prospects of development of hybrid NN/FEM programs are given at the end of paper.